Knowledge Thoughts and Attıtudes of Female Teachers Abaut Menapause: Elazig Yenimahalle Education and Research Health Center Area Case Study - Güngör, Leyla; Oğuzöncül, A. Ferdane; Açık, Yasemin; Güngör, M. Yüksel (Fırat University, 2002)
Aim: This study aims to find out female theachers, who works in primary and secondary schools in Yenimahalle Educatıon and Research Health Center area, and their knowledge, attitudes and thoughts abaut menapause. Material and Methods: 111 all of 140 teachers, who works in above mentioned area were subject to face-to-face interviewe. Response rate was is 79.3 per cent. Results: Sixty.three per cent of teachers (70 informant) describes menapause as the end of regl. According to them, women in menapause can show heavy vazomotor (75.7%) and psychological (57.7%) complaints. Abaut 82% of theachers indicadet that menapause reguires treatment. The preportion of theachers, who indicadet that sexual life activity of a women decreases in menapause, is 25.2% (28 informants). However preportion of informants who indicated no such a change is 47.7% (53 informants). Conclusion: Priority has to be given to the education and services on change in knowledge and attidudes about menapause and changes in this period in addition to necessarry applications to pass this period in happines and health.

Amaç: Elazığ Yenimahalle Eğitim ve Araştırma Sağlık Ocağı Bölgesi'nde bulunan İlköğretim ve Liselerde görev yapan bayan öğretmenlerin menopoz hakkındaki bilgi, tutum ve düşüncelerini saptamak amacıyla yapılmıştır. Gereç ve Yöntem: Söz konusu okullarda görev yapan toplam 140 bayan öğretmenden 111'ine ulaşılmış ve yüz yüze anket uygulanmıştır. Cevaplılık oranı %79.3'tür. Bulgular: Bayan öğretmenlerin %63.1 (70 kişi)'i menopozu adetin kesilmesi olarak tanımlamışlardır. Menopoza giren kadınlarda en çok vazomotor (%75.7) ve psikolojik şikayetler (%57.7) görüleceğini ifade etmişlerdir. Bayan öğretmenlerin %82.0 (91 kişi)'si menopozun tedavi edilmesi gerektiğini belirtmişlerdir. Menopoza giren bir kadında cinsel yaşamda azalma olur diyenlerin oranı %25.2 (28 kişi) iken değişmeyeceğini söyleyenlerin oranı %47.7 (53 kişi)'dir. Sonuç: Hem bayan öğretmenlerin, hem de genel populasyonun menopoz döneminde görülebilecek değişiklikler ve bu dönemin mutlu ve sağlıklı geçmesi için yapılması gerekenler konusunda bilgi ve tutumlarını değiştirici eğitim ve hizmet sunumuna öncelik verilmelidir.
ELAZIĞ YENİMAHALLE EĞİTİM VE ARAŞTIRMA SAĞLIK OCAĞI BÖLGESİNDE BULUNAN İLKÖĞRETİM VE LİSELERDE GÖREV YAPAN BAYAN ÖĞRETMENLERİN MENOPOZ HAKKINDAKİ BİLGİ, DÜŞÜNCE VE TUTUMLARI